Likelihood ratio determination for stochastic processes recognition problem with respect to the set of continuous and discrete memory observations; Informatica; Vol. 12, Iss. 2 - Dyomin N. S. Nikolas S. (2001, 2001)
This paper considers the problem of likelihood ratio determination for recognition of the stochastic processes with continuous time on the set continuous and discrete time memory observations. The research of memory influence on the detection quality of anomalous noises in the discrete channel observation with applying the general obtained results is realized for the one particular problem.